Al-Jumlah al-ʿArabiyyah - Abdul Haris (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2016)
This study aims to examine the concept of the Arabic sentence, its classifications, and methods of analysis, emphasizing the importance of sentence studies for learners of Arabic in understanding meaning and achieving grammatically accurate reading. The research employs a descriptive library research method by reviewing and describing the definitions and classifications of the Arabic sentence proposed by both classical and contemporary linguists, as well as the analytical approaches presented in relevant scholarly literature. The findings reveal notable differences between classical and modern Arab linguists regarding the definition of the Arabic sentence and its relationship to kalām (utterance). The study also identifies a contemporary classification of the Arabic sentence proposed by Muhammad Ibrahim ʿAbādah, which differs from the traditional classifications found in classical Arabic grammar. Furthermore, the research highlights two principal approaches to Arabic sentence analysis: the philosophical approach, which emphasizes grammatical justification and syntactic reasoning, and the descriptive approach, which focuses on describing sentence structures as they naturally occur without concentrating on the grammatical functions of individual words.